WEALTH MANAGMENT MARKET IN CHINA OPPORTUNITIES AND CHALLENGES - Dziawgo, Tomasz (Copernican Journal of Finance & Accounting, 2019)
As the key player in prospective Asia-Pacific market, China is becoming one of the most notable countries with regard to private banking services. In spite of being relatively young, Chinese wealth management market has been developing rapidly with increasing number of affluent clients and their value of total assets. Currently undergoing through transition between early development and maturity, Chinese wealth management market has several challenges to face in order to become a fully established one. The research objective of the article is to present the characteristics and potentia of Chinese wealth management market and to what extent does it correspond with global wealth management trends. The research method applied in the paper is an in-depth analysis of the case study regarding Chinese wealth management market with its’ potential and challenges. In order to carry out the analysis, various reports on the issue in question published by leading consulting companies, banks and experts were analyzed and relevant statistical data in the given period of time was examined as well. The outcome of the article is to list key steps for Chinese wealth management market to be taken, in order to elevate its’ status as one of the leading wealth management markets worldwide.